2023
DOI: 10.3390/foods12030517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Konjac Glucomannan/ε-Polylysine Hydrochloride/Ferulic Acid Composite Coating on the Freshness Preservation Performance and Flavor of Refrigerated Sea Bass Fillets

Abstract: Coating preservation has a remarkable effect on the preservation of aquatic products. This work prepared a composite coating using konjac glucomannan (KGM) as the film-forming matrix and ε-polylysine hydrochloride (ε-PL) and ferulic acid (FA) as the preservative. Three types of treated sea bass (KGM, KGM-ε-PL, and KGM-ε-PL-FA) and untreated sea bass were stored at 4 °C for 20 days to compare freshness changes under different treatment conditions. The results showed that the surface color and texture of sea bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Flavor analysis of cell-cultured fish meat was determined by a FlavourSpec gas chromatography-ion mobility spectrometry coupled instrument (GC-IMS), following the previous method with appropriate modifications. , Briefly, 5 g of sample was placed in a 20 mL headspace vial and incubated at 80 °C for 15 min at 500 rpm/min. The Restek MXT-WAX column was used for the separation of volatile organic compounds by aspirating 1 mL of gas in the injection needle at 85 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Flavor analysis of cell-cultured fish meat was determined by a FlavourSpec gas chromatography-ion mobility spectrometry coupled instrument (GC-IMS), following the previous method with appropriate modifications. , Briefly, 5 g of sample was placed in a 20 mL headspace vial and incubated at 80 °C for 15 min at 500 rpm/min. The Restek MXT-WAX column was used for the separation of volatile organic compounds by aspirating 1 mL of gas in the injection needle at 85 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental results showed that the composite films effectively inhibited the growth and reproduction of microorganisms and delayed the deterioration of large yellow croakers, thus extending the shelf life and enhancing economic benefits. Xiao et al [ 123 ] developed a composite coating using KGM as the film-forming matrix and ε-polylysine hydrochloride (ε-PL) and ferulic acid as the preservative. The composite coating successfully inhibited the formation of odor compounds such as 2-nonenone, isoamyl alcohol monomer, ammonia and trimethylamine, delaying the deterioration of fish and improving freshness.…”
Section: Application Of Kgm Gel In Aquatic Foodsmentioning
confidence: 99%